Pembelajaran Seni Tari Dalam Penerapan Kurikulum Merdeka di SMAN 1 Pangkalan Kuras - Della Agustia; Yahyar Erawati (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The aim of this research is to find out about cultural arts (dance) learning in the independent learning curriculum in class x 3 of SMAN 1 Pangkalan Kuras for the 2023/2024 academic year. This research uses qualitative descriptive research methods. The subjects in this research were class x3 students and arts and culture teachers at SMAN 1 Base Kuras. The results of this research are that in the independent learning curriculum, teachers are no longer fixated on books, but teachers can be more creative in teaching and students are expected to be able to make new discoveries. Learning in the Independent Curriculum uses teaching modules as a guide for learning in class. In learning, teachers also make what achievements they want in that semester. In class X 3, teachers use Phase E. Based on the results of this research, it was observed that teachers were starting to be able to adapt learning activities using the independent curriculum, even though there were still difficulties in compiling teaching modules, teachers were still able to use teaching module templates that had been provided by the government for students. It was observed that students had also adapted the learning curriculum accordingly. with what is taught.